Knight of Passion - Mallory, Margaret 1954- (New York Forever, 2010)
When Lady Linnet chooses revenge on those who destroyed her family over marrying her childhood sweetheart, Sir James Rayburn, she immediately regrets her decision and vows to make amends, but he refuses to trust her with his heart.
Keywords: Great Britain -- Man-woman relationships -- Manners and customs